Mulheres artistas brasileiras: poéticas artísticas e ensino/aprendizagem em arte - Andry Marcia Lopes (2023)
This master's research, entitled BRAZILIAN WOMEN ARTISTS: Artistic Poetics and Teaching/Learning in Art, aims to identify and expand possibilities of insertion of productions by Brazilian women artists in teaching/learning in Visual Arts in basic education schools. Part of the project's stages is the development of a Pedagogical Proposal with students in the 4th year of elementary school at the Lorenzo Fernândez State Conservatory of Music, in Montes Claros, Minas Gerais. It was possible to verify some stereotypes associated with artists that crossing the students' imagination, and at the same time understand how they perceived gender relations in art and society. After that, experiences were proposed based on the work of Brazilian women artists, considering artistic/poetic/critical issues about art, gender and diversity. As references for this study, we dialogued with researchers such as Barbosa (2019), Dias & Loponte (2019) and Louro (2003).